FOLK MUSICIANS IN UGANDA, by K. P. Wachsmann, Ph.D. (Uganda Museum Occasional Paper No. 2); the Uganda Museum, Kampala, 1956 (International Library of African Music, 1957)
pages: 58
Keywords: Folk music; Musicians; African Music; Uganda